MANAGEMENT OF EDUCATIONAL FACILITIES AND INFRASTRUCTURE: LITERATURE REVIEW ON EDUCATIONAL MANAGEMENT : Manajemen Sarana dan Prasarana - Yahya, Deya Pratama; Rahman, K.A Rahman; Mulyadi, Mulyadi (Indonesian Journal of Educational Development (IJED), 2023)
The research aimed to examine facilities and infrastructure management. Next, it applied qualitative writing methods and literature study or library research. The results of this study showed that the management of educational facilities and infrastructure in its application consisted of planning educational facilities and infrastructure, procurement of educational facilities and infrastructure, inventory of educational facilities and infrastructure, maintenance of educational facilities and infrastructure, elimination of educational facilities and infrastructure. In the process of teaching and learning activities, one of the factors that determined the success or failure of learning was the availability of learning facilities and infrastructure which were tools that could help and facilitate teaching and learning activities. Infrastructure and facilities were supports in the learning aspect.